Modeliranje in ocena vplivov razpršenih ukrepov zadrževanja in ponikanja padavinske vode na odtok iz urbanega povodja - Radinja, Matej (Acta hydrotechnica, 2017)
This paper presents the impacts of distributed retention and infiltration measures on urban runoff on a case study of the city of Girona, Spain. These measures, i.e. Sustainable Urban Drainage Systems (SUDS), reduce the quantity of water that would otherwise overflow from combined sewer system (CSS) into the recipient and in this way contribute to their quality. To assess their effectiveness the software Autodesk Storm and Sanitary Analysis 2016 was employed for developing an urban catchment model. Flow measurements were taken in the combined sewer overflow (CSO) channel for calibration. In accordance with the conditions in the urban catchment, which covers 2.7 km2, five scenarios were developed consisting of the following measures: infiltration basins, infiltration trenches, green roofs, and combinations thereof. The most efficient scenario in terms of overflow reduction per unit of implemented SUDS measure was the one including the combination of infiltration basins and infiltration trenches. Among scenarios with a single measure, infiltration basins were the most effective. In conclusion SUDS can significantly reduce CSOs while offering additional benefits. Therefore they should be included in the strategies of urban water management, i.e. in the design of urban drainage systems.
Keywords: combined sewer overflow; distributed measures; infiltration; padavinska voda; ponikanje; površinski odtok; rain water; razbremenilnik mešanega kanalizacijskega sistema; razpršeni ukrepi; retention; surface runoff; zadrževanje